Біоморфологічні особливості та поліваріантність розвитку Delphinium sergii Wissjul. (Ranunculaceae Juss.) ex situ - Gnatyuk, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to study biomorphologycal peculiarities and poly-variance of ontognesis of Delphinium sergii Wissjul. at M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Material and methods. It is investigated of ontogenesis and polymorphism of D. sergii plants in culture. Results.The poly-variance (structural and dynamical) in different individuals is discovered and described. The structural poly-variance is discovered in methods of reproduction, dimensional and morphological heterogeneity of even-aged individuals and individuals at one stage of ontogeny too. The dynamical poly-variance is manifested in a different rate of passage stages in ontogeny. The difference in the formation of inflorescences, shape and color of flowers and seeds, passing stages of ontogeny, size, reproduction and longevity in different individuals are showed. The different ways of creating a D. sergii bimorph in ontogeny is described. Conclusions. It is noted that for study of age structure on natural or introduction populations of D. sergii is sufficient consideration of the main species ontogenetic states. The study should be carried out before flowering of plants. For identification the ontogenetic states of individuals is possible to explore the aerial parts only (number, size, and degree dissected leaves blades). It is not for damaging the soil and plants.